Bioactive Lipids and Chronic Inflammation: Managing the Fire Within - Chiurchiù, Valerio; Leuti, Alessandro; Maccarrone, Mauro (Frontiers in Immunology, 2018)
Inflammation is an immune response that works as a contained fire that is pre-emptively sparked as a defensive process during infections or upon any kind of tissue insult, and that is spontaneously extinguished after elimination or termination of the damage. However, persistent and uncontrolled immune reactions act as a wildfire that promote chronic inflammation, unresolved tissue damage and, eventually, chronic diseases. A wide network of soluble mediators, among which endogenous bioactive lipids, governs all immune processes. They are secreted by basically all cells involved in inflammatory processes and constitute the crucial infrastructure that trigger, coordinate and confine inflammatory mechanisms. However, these molecules are also deeply involved in the detrimental transition from to chronic inflammation, be it for persistent or excessive action of pro-inflammatory lipids or for the impairment of the functions carried out by resolving ones. As a matter of fact, bioactive lipids have been linked, to date, to several chronic diseases, including rheumatoid arthritis, atherosclerosis, diabetes, cancer, inflammatory bowel disease, lupus and multiple sclerosis. This review summarizes current knowledge on the involvement of the main classes of endogenous bioactive lipids – namely classical eicosanoids, pro-resolving lipid mediators, lysoglycerophospholipids/sphingolipids and endocannabinoids – in the cellular and molecular mechanisms that lead to the pathogenesis of chronic disorders.